Platform capitalism: The intermediation and capitalisation of digital economic circulation - Paul Langley; Andrew Leyshon (Finance and Society, 2017)
A new form of digital economic circulation has emerged, wherein ideas, knowledge, labour and use rights for otherwise idle assets move between geographically distributed but connected and interactive online communities. Such circulation is apparent across a number of digital economic ecologies, including social media, online marketplaces, crowdsourcing, crowdfunding and other manifestations of the so-called ‘sharing economy’. Prevailing accounts deploy concepts such as ‘co-production’, ‘prosumption’ and ‘peer-to-peer’ to explain digital economic circulation as networked exchange relations characterised by their disintermediated, collaborative and democratising qualities. Building from the neologism of platform capitalism, we place ‘the platform’ — understood as a distinct mode of socio-technical intermediary and business arrangement that is incorporated into wider processes of capitalisation — at the centre of the critical analysis of digital economic circulation. To create multi-sided markets and coordinate network effects, platforms enrol users through a participatory economic culture and mobilise code and data analytics to compose immanent infrastructures. Platform intermediation is also nested in the ex-post construction of a replicable business model. Prioritising rapid up-scaling and extracting revenues from circulations and associated data trails, the model performs the structure of venture capital investment which capitalises on the potential of platforms to realise monopoly rents.